Early molecular diagnosis of BRAF status drives the neurosurgical management in BRAF V600E-mutant pediatric low-grade gliomas: a case report - Gianluca Piccolo; Antonio Verrico; Giovanni Morana; Gianluca Piatelli; Patrizia De Marco; Valentina Iurilli; Manila Antonelli; Gabriele Gaggero; Antonia Ramaglia; Marco Crocco; Samuele Caruggi; Claudia Milanaccio; et al. (BMC Pediatrics, 2022)
Abstract Background To date, this is the only report showing with close and consecutive magnetic resonance images the extremely rapid response of two types of pediatric low-grade gliomas (PLGG) to vemurafenib and its impact on the surgical approach. Cases presentation We report two cases of symptomatic PLGG treated with vemurafenib, a BRAF inhibitor: in a 12-year-old girl it was used as first-line medical treatment, reducing the tumor by 45% within a month and stabilizing to 76% after a year; in a 3-year-old boy with no improvement after SIOP LGG 2004 Protocol, vemurafenib induced in only one week a 34% shrinkage and solved the hydrocephalus, avoiding surgical operation. Discussion and conclusions Our cases demonstrate how an early molecular diagnosis of BRAF mutations through the neurosurgical biopsy is essential to promptly start targeted therapies., whose effect can influence both therapeutic and surgical decisions, hopefully reducing the occurrence of second neurosurgery with associated risks of neurological sequelae.